Why is the Social Inclusion Policy of Lithuania Precisely the Way it is? - Poviliūnas, Arūnas (Socialinė teorija, empirija, politika ir praktika, 2017)
In order to reveal the dichotomy of convergence and divergence, the article discusses the profile of Lithuanian social inclusion policy. The article critically evaluates the Open Method of Coordination and the new social policy tool, which is still under the process of elaboration – the European Pillar for Social Rights. The concrete examples of Lithuanian social policy that suit the definition of the austerity measures reveal that instead of a promoted and supposed convergence towards Social Europe, the European policies of social inclusion diverge. In order to explain the diverging social policies and their institutional constellations, the theory of path dependency, one that emphasizes the transaction costs and typology of social knowledge, is employed. The article also aims to elaborate the theoretical framework for the examination of the relationship between the profile of social inclusion policy and value orientations of the population. Lithuanian policy experts of social inclusion, as well as professionals working in the same field of social policy, are inclined to prioritize the austerity measures and the role of social control.